2010
DOI: 10.1186/1471-2466-10-22
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin as a prognostic marker in patients with pulmonary arterial hypertension

Abstract: BackgroundLiver dysfunction reflects the status of heart failure, with congestion and low perfusion of the liver serving as causative mechanisms. Previous studies demonstrated relationship between the results of liver function test and the prognosis in patients with heart failure. However, few studies have examined this relationship in patients with pulmonary arterial hypertension (PAH).MethodsThe subjects were 37 patients with PAH (8 men and 29 women; 18 with idiopathic PAH and 19 with connective tissue disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 15 publications
(17 reference statements)
4
55
1
2
Order By: Relevance
“…Alkaline phosphatase and ferritin were elevated in subjects with SCD with PH and were risk factors for death in the univariate and multivariate analyses, confirming previous findings from echocardiography (4). Another previously identified risk factor, direct bilirubin, reflects an association observed in precapillary PH without SCD (52). Increasing age is reported with an increased risk of PH in previous studies (2, 4), but mortality was not explained by old age among patients with PH in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Alkaline phosphatase and ferritin were elevated in subjects with SCD with PH and were risk factors for death in the univariate and multivariate analyses, confirming previous findings from echocardiography (4). Another previously identified risk factor, direct bilirubin, reflects an association observed in precapillary PH without SCD (52). Increasing age is reported with an increased risk of PH in previous studies (2, 4), but mortality was not explained by old age among patients with PH in our study.…”
Section: Discussionsupporting
confidence: 80%
“…In a study by Takeda et al (18), it was found that total bilirubin was a prognostic marker in patients with PAH, while S-LDH was not (18); in the present study, however, S-LDH was found to be a more effective prognostic marker than total bilirubin. This difference may have been due to the fact that the study by Takeda et al (18) included patients with connective tissue disease-associated PAH in addition to patients with IPAH, and because fewer patients were recruited by Takeda et al (18) compared with the number of patients in the present study (37 vs. 173). The present study also demonstrated that S-LDH was a more effective predictor of mortality than NT-proBNP in patients with IPAH.…”
Section: Discussioncontrasting
confidence: 45%
“…The association between bilirubin and the rate of mortality or incidence of stroke was different between genders (22). In addition, other groups have suggested that hyperbilirubinemia is linked to pulmonary arterial hypertension and chronic heart failure (23,24). Therefore, the purpose of this study was to investigate whether or not the serum bilirubin level is independently associated with baPWV in established CAD.…”
Section: Introductionmentioning
confidence: 92%